Comparative Analysis of Laparoscopic and Open Approaches in Emergency Abdominal Surgery. Issue 10 (October 2017) - Siletz, Anaar; Grotts, Jonathan; Lewis, Catherine; Tillou, Areti; Cryer, Henry Magill; Cheaito, Ali
The objective of this study was to evaluate usage and outcomes of emergency laparoscopic versus open surgery at a single tertiary academic center. Over a three-year period 165 patients were identified retrospectively using National Surgical Quality Improvement Program results. Appendectomies and cholecystectomies were excluded. Open and laparoscopic approaches were compared regarding preoperative and operative characteristics, the development of postoperative complications, 30-day mortality, and length of hospital stay. Indications for operation were similar between groups. Patients who underwent open surgery had more severe comorbidities and higher ASA class. Laparoscopy was associated with reduced complication rates, operative time, length of stay, and discharges to skilled nursing facilities on univariate analysis. In a multivariate model, surgical approach was not associated with the development of complications. Older age, dependent status, and dyspnea were predictors of conversion from attempted laparoscopic to open approaches.